COVID-19 in children: Could pertussis vaccine play the protective role?. (December 2020) - Ismail, Mohamad Bachar; Omari, Sarah Al; Rafei, Rayane; Dabboussi, Fouad; Hamze, Monzer
Abstract: While COVID-19 continues to spread across the globe, diligent efforts are made to understand its attributes and dynamics to help develop treatment and prevention measures. The paradox pertaining to children being the least affected by severe illness poses exciting opportunities to investigate potential protective factors. In this paper, we propose that childhood vaccination against pertussis (whooping cough) might play a non-specific protective role against COVID-19 through heterologous adaptive responses in this young population. Pertussis is a vaccine-preventable infectious disease of the respiratory tract and it shares many similarities with COVID-19 including transmission and clinical features. Although pertussis is caused by a bacterium ( Bordetella pertussis ) while COVID-19 is a viral infection (SARS-CoV-2), previous data showed that cross-reactivity and heterologous adaptive responses can be seen with unrelated agents of highly divergent groups, such as between bacteria and viruses. While we build the arguments of this hypothesis on theoretical and previous empirical evidence, we also outline suggested lines of research from different fields to test its credibility. Besides, we highlight some concerns that may arise when attempting to consider such an approach as a potential public health preventive intervention against COVID-19.